Forms of Verbal Violence in Student Conversations on WhatsApp Groups: Pragmatic Study - Pattisahisiwa, Maimuna; Sasabone, Carolina; Pattiasina, Petrus Jacob (Universitas Pattimura, 2025)
Verbal communication is communication that involves words, both spoken and written. Social media can be stated to play a complete function in human existence every day in the current era like now. Social media is the most popular and widely used communication medium by various segments of society in the current period. Thru social media, users can express themselves. Within the WhatsApp group, numerous pupils were found to have communication involving kinds of aggression in different ways of speaking. Usually, people are free to express themselves trough words. This study analyzes kinds of violence in the chats of students in the WhatsApp group of Program Studi Pendidikan Bahasa dan Sastra Indonesia, Class of 2020. This is classified as qualitative descriptive research. The research to be conducted is qualitative research because the data collected is not numbers but words, phrases, sentences, and. The data source in this study is students from the Program Studi Pendidikan Bahasa dan Sastra Indonesia in a WhatsApp group called (PBSI Class of 2020).